Anode curvature influence on characteristics of negative corona discharge under Trichel pulsed mode - Golota, V.I.; Bolotov, O.V. (Вопросы атомной науки и техники, 2011)
Experimental investigations of electrodynamics characteristics of negative corona discharge in air under Trichel pulsed mode are presented. The influence of anode dimensions and curvature on discharge current parameters in strongly non-uniform electric field was studied. It was shown that at the same conditions the decreasing of anode curvature causes the increasing of current pulses frequency. At the same time the parameters of Trichel pulses remain constant for different anode curvatures. The increasing of average discharge current value under decreasing of anode curvature also observed. It is necessary to note that the variation of anode dimensions has a proportional action on current pulses frequency; however it is observed only in a certain range of the applied voltage.